An Identification of Relationship Between Regional Development Level and Slums in Sidenreng Rappang Regency - Rika Riyanti Anwar; Ria Wikantari; Mahyuddin Mahyuddin (Journal of Applied Engineering and Technological Science (JAETS), 2022)
Sidenreng Rappang Regency, South Sulawesi Province was recorded to be ranked 2nd (second) as the regency/city with the highest slum area in South Sulawesi in 2020.The development of the Sidenreng Rappang Regency area as a strategic agribusiness center area with economic activity with high mobility and the increasing need for land for large-scale production facilities and housing development is suspected to have implications for the existence of this slum settlement. This study aims to identify the relationship between the level of regional development and slums in Sidenreng Rappang Regency. The research method used is a scalogram analysis on the variables of population, distance and travel time, educational, social, economic, health, and agribusiness support facilities in each village/urban village which produces the value of the Urban Village Development Index (IPK) and Village/Urban Village Hierarchy. Furthermore, the relationship between the development level and the slum area was identified through a Pearson Correlation between the IPK value and the village/urban village slum area. The results showed that the Village Development Index (IPK) with the percentage of slum area is not correlated or it can be concluded that the level of regional development has no relationship with the slums in Sidenreng Rappang Regency.